2011
DOI: 10.1097/mrr.0b013e3283487f31
|View full text |Cite
|
Sign up to set email alerts
|

Review of self-awareness and its clinical application in stroke rehabilitation

Abstract: The objectives of this study were (i) to explore, following a literature review, the concepts of self-awareness, its assessment, and intervention for self-awareness deficits, as well as its clinical significance in stroke rehabilitation; and (ii) to apply the concepts of self-awareness in the context of a rehabilitation program. The search was conducted by the electronic databases Web of Science, Science Direct, MEDLINE, and PsychcInfo. A systematic literature search of publications written in English between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 20 publications
(40 reference statements)
1
36
0
1
Order By: Relevance
“…As noted in previous reviews, researchers used different interventions to address impaired self-awareness. 27 The majority of the treatments included a combination of psychoeducation and feedback.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted in previous reviews, researchers used different interventions to address impaired self-awareness. 27 The majority of the treatments included a combination of psychoeducation and feedback.…”
Section: Discussionmentioning
confidence: 99%
“…38,43 In one study, patients were included if they underestimated their memory deficits (incongruence between predicted memory performance and actual performance), 40 and in another study, patients had a SADI score greater than 0 (mean SADI score at baseline was 5). 25 Furthermore, studies reported high SRSI scores (range: 6-10), 42,44 high SADI scores (8), 39 and a large difference score on the AQ (range: [22][23][24][25][26][27][28][29][30] 42 at baseline. In 2 studies, baseline levels of awareness were not specified.…”
Section: High-quality Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have explored the relationship between metacognition and stroke location, type and severity, or its clinical application in stroke care and rehabilitation 15 16. Stroke survivors may be particularly susceptible to metacognitive deficits, as neuropsychological disorders such as magnitude estimation deficit,17 anosognosia or anosodiaphoria, spatial neglect, and problems with emotional semantics and abstraction in stroke, are common 15.…”
Section: Introductionmentioning
confidence: 99%
“…Suggestive of the status and influence of the medical model of disability (Brandon and Pritchard 2011;Schuelka 2015), studies have considered the role of various person-related factors in aiding and/or impeding community reintegration including physical function (Carter et al 2000;Ostir et al 2005), mental health (Carter et al 2000), cognitive ability (robison et al 2009), self-efficacy (Pang, eng, and Miller 2007) and self-awareness (Leung and Liu 2011). Certain factors external to the individual, including social and professional support, have also attracted a degree of attention (Chau et al 2009;ellis-Hill et al 2009;nicholson et al 2013;robison et al 2009;Walsh et al 2014).…”
Section: Introductionmentioning
confidence: 99%